2014
DOI: 10.1007/s00192-014-2373-2
|View full text |Cite
|
Sign up to set email alerts
|

Dyspareunia and pelvic floor muscle function before and during pregnancy and after childbirth

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Tennfjord, M. K., Hilde, G., Staer-Jensen, J., Ellstrøm Engh, M., Bø, K. (2014).Dyspareunia and pelvic floor muscle function before and during pregnancy and during pregnancy and after childbirth. ABSTRACT Introduction and hypothesis:There is limited knowledge on dyspareunia during pregnancy and postpartum and the role of the pelvic floor muscles (PFM) in women with dyspareunia. Aims of the study were to investigate presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 30 publications
2
23
1
8
Order By: Relevance
“…In this study, most primiparous women returned to sexual activity between 50 and 70 days after delivery and about half of them mentioned dyspareunia, however, as with other studies 10 , 15 , no difference was found in PFMS related to the type of childbirth regarding this complaint.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In this study, most primiparous women returned to sexual activity between 50 and 70 days after delivery and about half of them mentioned dyspareunia, however, as with other studies 10 , 15 , no difference was found in PFMS related to the type of childbirth regarding this complaint.…”
Section: Discussionsupporting
confidence: 46%
“…No significant difference was identified between the groups in relation to vaginal pressure at rest, perineal muscle strength and vaginal endurance, six and 12 months after delivery. Also, no significant difference was identified between the groups according to the delivery type, episiotomy, third and fourth degree perineal lacerations, or weight of the newborn 10 . …”
Section: Introductionmentioning
confidence: 77%
“…Mode of delivery gave minimal risk of having sexual dysfunction in this study, except for the women reporting vaginal laxity where vaginal delivery and forceps showed a fourfold increased risk when compared with caesarean section [6]. Dyspareunia has been found to be associated with lacerations following vaginal delivery [7], but the published literature is controversial [6,8,9].…”
Section: Introductionmentioning
confidence: 59%
“…However, there may also be an overlap of symptoms from the questionnaire ICIQ‐VS, meaning that more symptoms may have similar explanations. No association has been found between PFM function and breastfeeding among the same women [9].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation